Patogenisitas isolat bakteri entomopatogenik Bacillus thuringiensis diisolasi dari Spodoptera litura terhadap larva Plutella xylostella (Lepidoptera:Plutellidae) - Yulia Pujiastuti; Suparman SHK; Dwi Probowati Sulistyani (Seminar Nasional Lahan Suboptimal, 2021)
Pujiastuti Y, SHK Suparman, Sulistyani DP. 2021. Patogenicity of entomopathogenic Bacillus thuringiensis isolated from Spodoptera litura against Plutella xylostella larvae (Lepidoptera:Plutellidae). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 621-627. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Diamondback moth, Plutella xylostella is an important insect pest on plants belong to Brassicaceae family. Symptoms of attack is hollow leaves and leave dirt on them. If it is not controlled, the yield loss can reach 80%. Control by using biological agents entomopathogenic bacteria Bacillus thuringiensis may be used to reduce the population of P. xylostella. The purpose of research was to study the pathogenicity of B. thuringiensis isolated from cadaver of  Spodoptera litura against P. xylostella larvae in the laboratory. The treatments were two isolates of B. thuringiensis encoded  SlBt01 and SLBt03. The experiment was designed with a completely randomized design  (CRD) separated between isolates. The treatment consisted of 5 treatments (including control) spore density and 5 replications. Observations were mortality rate and time of death of the test larvae. Results showed the highest mortality was in isolate SlBT01 (61.73%)  and in isolate SlBt03 (56.66%). The lowest LT50 values of isolates SlBt01 and SLBt03 were 9.78 days and 9.14 days, respectively. Symptoms of infection in Plutella larvae are changes in body color and eventually die with symptoms of wet rot.